Hybrid Intelligence Proceedings of the 4th International Conference on Computational Design and Robotic Fabrication (CDRF 2022) - Yuan, Philip F.; Chai, Hua; Yan, Chao; Li, Keke; Sun, Tongyue (Computational Design and Robotic Fabrication, 2023)
This open access book is a compilation of selected papers from DigitalFUTURES 2022-The 4th International Conference on Computational Design and Robotic Fabrication (CDRF 2022). The work focuses on novel techniques for computational design and robotic fabrication. The contents make valuable contributions to academic researchers, designers, and engineers in the industry. As well, readers encounter new ideas about intelligence in architecture.